PERTANGGUNGJAWABAN PIDANA BAGI PELAKU TINDAK PIDANA PERTAMBANGAN MINERAL DAN BATUBARA (ANALISIS PUTUSAN PN PRAYA NOMOR 123/PID. B/LH/2023/PN PYA) - MEGAYATI, DHINA; LESTARI, B. FARHANA KURNIA; ARSITHA, REILITA DWI (Universitas Mahasaraswati K. Mataram, 2024)
The mining sector is one of the supports for the welfare of the Indonesian people. Therefore, mining activities must be carried out according to procedures and have legality as applicable regulations. Criminal liability for perpetrators of mineral and coal mining crime Analysis of Decision Number 123/Pid.B/LH/2023/PN Pya is that the defendant has been proven guilty and fulfills the elements in Article 160 of Law of the Republic of Indonesia Number 3 of 2020 concerning amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining. Criminal liability for case Number 123/Pid.B/LH/2023/PN Pya that the Defendant has been proven guilty and meets the elements in Article 160 of Law of the Republic of Indonesia Number 3 of 2020 concerning amendments to Law of the Republic of Indonesia Number 4 of 2009 concerning Mineral and Coal Mining, namely the provision that Every person who has an IUP or IUPK at the Exploration activity stage but carries out Production Operation activities shall be punished with a maximum imprisonment of 5 (five) years and a maximum fine of IDR 100,000,000,000.00 (one hundred billion rupiah). When associated with the maximum penalty, the penalty imposed on the Defendant is still relatively low because mining without a permit is a very serious case and has a major impact on the state and society. The judge's consideration in imposing a criminal sentence based on juridical and non-juridical considerations, the judge decided that the defendant was sentenced to imprisonment of 7 (seven) months and a fine of Rp. 20,000,000.00 (twenty million rupiah) subsidair 2 (two) months.